Morphological characteristics and habitats of red seaweed gracilaria spp. (gracilariaceae, rhodophyta) in santubong and asajaya, sarawak, malaysia - Muhammad Nur, Arif Othman; Ruhana, Hassan; Mohd Nasarudin, Harith; Amir Shah Ruddin, Md Sah (Penerbit Universiti Sains Malaysia, 2018)
Red seaweed Gracilaria, one of the largest genus in Division Rhodophyta inhabits Sarawak coastal water. This study was designed to identify the species of Gracilaria using morphological approach and to assess selected water quality parameters in Gracilaria habitats. Three field samplings were carried out in Santubong and Asajaya, Sarawak from November 2013 to December 2014. Overall, three species were identified namely Gracilaria changii, G. blodgettii and G. coronopifolia, attached to net of cage culture in Santubong and root of mangrove trees in Asajaya. In addition, three different taxa of aquatic macroinvertebrates (polychaete, small crab, bivalve) and single species of red seaweed (Acanthophora sp.) were observed in Gracilaria assemblages. An estimate of 37% to 40% of the upper part of the cage net in Santubong was covered by seaweeds and only 16% to 20% in Asajaya’s mangrove. The study had provided better information on identification of Gracilaria and their habitat in Sarawak. Future work involving DNA barcoding of each species is in progress. © Penerbit Universiti Sains Malaysia, 2018.